2017
DOI: 10.1136/archdischild-2017-312916
|View full text |Cite
|
Sign up to set email alerts
|

Academic performance of children born preterm: a meta-analysis and meta-regression

Abstract: BackgroundAdvances in neonatal healthcare have resulted in decreased mortality after preterm birth but have not led to parallel decreases in morbidity. Academic performance provides insight in the outcomes and specific difficulties and needs of preterm children.ObjectiveTo study academic performance in preterm children born in the antenatal steroids and surfactant era and possible moderating effects of perinatal and demographic factors.DesignPubMed, Web of Science and PsycINFO were searched for peer-reviewed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
125
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(150 citation statements)
references
References 40 publications
14
125
6
Order By: Relevance
“…However, this is unlikely, as others have found poorer than expected mathematics achievement among older children and adolescents who were born preterm (Akshoomoff et al, 2017;Litt et al, 2012;Taylor et al, 2009). Similar to our findings, a meta-analysis of 17 studies found that arithmetic performance of preterm children and adolescents (6-18 years of age) was 0.71 SD below full-term controls (Twilhaar, Kieviet, Aarnoudse-Moens, Elburg, & Oosterlaan, 2018). This hints towards persistent lower performance in complex mathematics skills following preterm birth.…”
Section: Discussionsupporting
confidence: 89%
“…However, this is unlikely, as others have found poorer than expected mathematics achievement among older children and adolescents who were born preterm (Akshoomoff et al, 2017;Litt et al, 2012;Taylor et al, 2009). Similar to our findings, a meta-analysis of 17 studies found that arithmetic performance of preterm children and adolescents (6-18 years of age) was 0.71 SD below full-term controls (Twilhaar, Kieviet, Aarnoudse-Moens, Elburg, & Oosterlaan, 2018). This hints towards persistent lower performance in complex mathematics skills following preterm birth.…”
Section: Discussionsupporting
confidence: 89%
“…Preterm birth and low birthweight co‐occur frequently, with 69.2% of children born preterm also being born with a low birthweight and 49.8% of children born with a low birthweight also being born preterm . Preterm birth and/or low birthweight survivors are at high risk of adverse cognitive, academic, and behavioural outcomes . Children born preterm/low birthweight have 0.8 standard deviation (SD) lower IQ scores and perform about a 0.5 SD poorer than term‐born peers on mathematics, reading, and spelling tests .…”
mentioning
confidence: 99%
“…3 Preterm birth and/or low birthweight survivors are at high risk of adverse cognitive, academic, and behavioural outcomes. 1,4,5 Children born preterm/low birthweight have 0.8 standard deviation (SD) lower IQ scores and perform about a 0.5 SD poorer than term-born peers on mathematics, reading, and spelling tests. 4,5 Also, a two to four times higher risk of being diagnosed with attention-deficit/hyperactivity disorder than for term-born peers has been reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The early identification of a preterm profile characterised by inattentive ADHD symptomatology associated with lower IQ and perinatal clinical risk suggests the need for early screening and educational interventions aimed at improving specific attention problems in very preterm children, many of whom exhibit academic difficulties at school age and are three times more likely to have special educational needs than their term-born peers (51). Attention is a crucial requirement in school settings as it allows the child to engage with classroom education activities.…”
Section: Discussionmentioning
confidence: 99%